Exploring multimodal collaborative storytelling with Pepper: a preliminary study with zero-shot LLMs - Zabala, Unai; Echevarria, Juan; Rodriguez, Igor; Lazkano, Elena (Frontiers in Robotics and AI, 2025)
With the rise of large language models (LLMs), collaborative storytelling in virtual agents or chatbots has gained popularity. Despite storytelling has long been employed in social robotics as a means to educate, entertain, and persuade audiences, the integration of LLMs into such platforms remains largely unexplored. This paper presents the initial steps for a novel multimodal collaborative storytelling system in which users co-create stories with the social robot Pepper through natural language interaction and by presenting physical objects. The robot employs a YOLO-based vision system to recognize these objects and seamlessly incorporate them into the narrative. Story generation and adaptation are handled autonomously using the Llama model in a zero-shot setting, aiming to assess the usability and maturity of such models in interactive storytelling. To enhance immersion, the robot performs the final story using expressive gestures, emotional cues, and speech modulation. User feedback, collected through questionnaires and semi-structured interviews, indicates a high level of acceptance.